2021
DOI: 10.1186/s13046-021-02012-7
|View full text |Cite
|
Sign up to set email alerts
|

Metformin induces Ferroptosis by inhibiting UFMylation of SLC7A11 in breast cancer

Abstract: Background Ferroptosis is a newly defined form of regulated cell death characterized by the iron-dependent accumulation of lipid peroxidation and is involved in various pathophysiological conditions, including cancer. Targeting ferroptosis is considered to be a novel anti-cancer strategy. The identification of FDA-approved drugs as ferroptosis inducers is proposed to be a new promising approach for cancer treatment. Despite a growing body of evidence indicating the potential efficacy of the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(101 citation statements)
references
References 64 publications
0
86
0
Order By: Relevance
“…Mechanistically, in the present study, we revealed that the activation of NRF2 weakened radiation-induced ROS generation and lipid peroxidation, alleviating RT-induced ferroptosis and promoting radioresistance in ESCC. We additionally proposed that activated NRF2 could directly combine with the promoter region of SLC7A11 to regulate its transcription, which is related to the inhibition of ferroptosis [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, in the present study, we revealed that the activation of NRF2 weakened radiation-induced ROS generation and lipid peroxidation, alleviating RT-induced ferroptosis and promoting radioresistance in ESCC. We additionally proposed that activated NRF2 could directly combine with the promoter region of SLC7A11 to regulate its transcription, which is related to the inhibition of ferroptosis [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysates of the IHH4 cells and BCPAP cells were added to SDS-PAGE sample loading buffer (Beyotime, Shanghai, China) and boiled at 100 °C for 8–10 min. Western blotting was conducted as previously described[ 24 , 25 ]. The following antibodies were showed in supported information, and anti-actin as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Starvation of cystine reduces the level GSH by directly decreasing synthesis and the GCN2-eIF2α-ATF4-CHAC1 pathway, thereby inducing ferroptosis in TNBC cells ( Chen et al, 2017 ). The anti-diabetic drug metformin reduces the stability of xCT by inhibiting its UFMylation, thus inducing ferroptosis and inhibiting the proliferation of breast cancer cells ( Yang et al, 2021 ). In contrast, MUC1-C, a transmembrane protein, can maintain the GSH level and redox balance by forming a complex with xCT and the CD44 variants (CD44v), which inhibits ferroptosis in breast cancer cells ( Ishimoto et al, 2011 ).…”
Section: Role Of Ferroptosis In Cancersmentioning
confidence: 99%